1990
DOI: 10.1901/jeab.1990.53-201
|View full text |Cite
|
Sign up to set email alerts
|

Choice With Uncertain Outcomes: Conditioned Reinforcement Effects

Abstract: Pigeons responded on concurrent chains with equal initial- and terminal-link durations. In all conditions, the terminal links of one chain ended reliably in reinforcement; the terminal links on the alternative chain ended in either food or blackout. In Experiment 1, the terminal-link stimuli were correlated with (signaled) the outcome, and the durations of the initial and terminal links were varied across conditions. Preference did not vary systematically across conditions. In Experiment 2, terminal-link durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
137
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(153 citation statements)
references
References 41 publications
11
137
5
Order By: Relevance
“…Overall, many of the results obtained fit well with both Mazur's (1989Mazur's ( , 1991 model and the local delayreduction approach proposed by Dunn and Spetch (1990). Mazur's model provides a more parsimonious account than that offered by the delay-reduction framework for the effect of varying BOTL duration in unsignaled procedures and the lack of effect of this same manipulation within signaled procedures.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Overall, many of the results obtained fit well with both Mazur's (1989Mazur's ( , 1991 model and the local delayreduction approach proposed by Dunn and Spetch (1990). Mazur's model provides a more parsimonious account than that offered by the delay-reduction framework for the effect of varying BOTL duration in unsignaled procedures and the lack of effect of this same manipulation within signaled procedures.…”
Section: Discussionsupporting
confidence: 66%
“…Because between-subject variability is typically high, we cannot strongly argue against these predictions on the basis of the results presented here. It is noteworthy, however, that in each of the present experiments, as well as in those of Dunn and Spetch (1990), Kendall (1974Kendall ( , 1985, and Spetch et al (1990), mean choice proportions for the 50% side were above .5 in all signaled conditions with equal terminal links of 30 sec or longer. Furthermore, in a recent study (Belke, 1992;Belke & Spetch, 1994), 6 out of 8 pigeons displayed a strong preference for the 50% alternative in a variant of the present procedure in which they were forced to remain on the 50% side after they chose it until a food outcome occurred.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Indeed, unreliable reinforcement may be more typical in instructional and clinical situations than reliable reinforcement. Research has shown that nonhuman subjects are likely to prefer unreliable reinforcement to reliable reinforcement when conditioned reinforcers are presented during delay intervals preceding the availability of the unreliable reinforcement (Belke & Spetch, 1994;Dunn & Spetch, 1990). Little applied research has been conducted in this area, however.…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 99%